Enhancing social awareness development through multicultural literature. Issue 3 (27th May 2021) - Linder, Roberta
Abstract: This article provides a research basis and practical applications for the inclusion of multicultural literature as a component of SEL programming. Multicultural text selections not only allow young adolescents to see themselves and others through the characters, but they also provide students with the opportunity to take part in activities and discussions that can help foster their social awareness development. I also provide suggestions of picture books, graphic novels, poetry, and novels, along with a list of applicable children's literature awards.